A Self-Powered Medical Device for Blood Irradiation Therapy. (27th June 2012) - Amsel, Avigail D.; Rudnitsky, Arkady; Zalevsky, Zeev
Abstract : Implantable wireless devices may allow localized real-time biomedical treating and monitoring. However, such devices require a power source, which ideally, should be self-powered and not battery dependent. In this paper, we present a novel self-powered light therapeutic device which is designed to implement blood irradiation therapy. This device is self-powered by a miniaturized turbine-based generator which uses hydraulic flow energy as its power source. The research presented in this paper may become the first step towards a new type of biomedical self-operational micromechanical devices deployed for biomedical applications.